2002
DOI: 10.1159/000066276
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Cytoskeleton and of Protein Phosphorylation Events in the Osmotic Stress Response in EEL Intestinal Epithelium

Abstract: The eel intestinal epithelium responds to an acute hypertonic challenge by a biphasic increase of the rate of Cl- absorption (measured as short circuit current, Isc, and creating a negative transepithelial potential, Vte, at the basolateral side of the epithelium). While the first, transient phase is bumetanide-insensitive, the second, sustained phase is bumetanide-sensitive, reflecting activation of the apically located Na+-K+-2Cl- (NKCC) cotransporter, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 47 publications
1
42
0
Order By: Relevance
“…Therefore, our observation supports the notion that Ostf induction is dependent on the integrity of the cytoskeleton, which is modulated in the process of cell volume regulation. Using eel intestinal epithelia, Lionetto et al reported that colchicine treatment inhibited the hypertonicity-induced shortcircuit current by about 50-80% (Lionetto et al, 2002). This observation supports the important role of the cytoskeleton in cellular osmo-responses.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, our observation supports the notion that Ostf induction is dependent on the integrity of the cytoskeleton, which is modulated in the process of cell volume regulation. Using eel intestinal epithelia, Lionetto et al reported that colchicine treatment inhibited the hypertonicity-induced shortcircuit current by about 50-80% (Lionetto et al, 2002). This observation supports the important role of the cytoskeleton in cellular osmo-responses.…”
Section: Discussionmentioning
confidence: 79%
“…Consistently, the incubation abolished the induction of Ostf mRNA expression. Since the change in intracellular ion strength would affect cell volume and cytoskeleton architecture (Di Ciano et al, 2002;Lionetto et al, 2002;Tse et al, 2006), we decided to test the effect of colchicine (an inhibitor of microtubule polymerization) to hypertonicityinduced Ostf expression. Obviously, colchicine treatment reduced Ostf gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that inhibition of the MLCK pathway altered the expression levels of Na + /K + -ATPase and TauT mRNA. Intriguingly, the osmotic stress response in eel intestinal epithelia was also found to be modulated by inhibitors of MLCK (Lionetto et al, 2002). In the mammalian system, hyperosmotic stress stimulated MLC2 phosphorylation and NKCC activity to facilitate cell volume restoration (Hoffmann and Pedersen, 2007).…”
Section: Effects Of Hypertonic Stress and Protein Kinase Inhibitors Omentioning
confidence: 99%
“…In eel intestine, chelerythrine and calyculin A were potent inhibitors of the activation of NKCC-mediated ion uptake in an RVI response to hypertonic shock (Lionetto et al, 2002). In human cervical cancer cells, hypotonic shock evokes activation of extracellular signal activated kinase (ERK1 and ERK2) and p38 MAPK through a PKC-dependent pathway that also involves intracellular calcium (Shen et al, 2001).…”
Section: Protein Kinase C and Myosin Light Chain Kinasementioning
confidence: 99%